2021
DOI: 10.1002/aepp.13185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changes in Title II of the 2018 Farm Bill on the acreage and environmental benefits of Conservation Reserve Program

Abstract: The 2018 Farm Bill lowered the maximum rental payments for the Conservation Reserve Program (CRP) by 10%-15% and increased the acreage enrollment cap by 3 million acres. We show that CRP acreage will decrease by 1.18 million acres (associated with a 3.3% environmental benefit decrease of the CRP) as a result of the rental rate reduction and that CRP acreage will increase by 2.32 million acres (associated with a 6.2% environmental benefit increase of the CRP) because of the acreage cap increase. The largest imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For instance, Jang and Du (2018) found a negative relationship between growing degree days and CRP participation. In contrast, Cornish et al (2022) found a mixed association between growing degree days and CRP acreage but with varying statistically significant levels across different agricultural regions. As expected, we find a positive relationship between the national CRP enrollment cap and CRP acreage, as a 1% increase in the national cap increases CRP acreage by 0.09%.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…For instance, Jang and Du (2018) found a negative relationship between growing degree days and CRP participation. In contrast, Cornish et al (2022) found a mixed association between growing degree days and CRP acreage but with varying statistically significant levels across different agricultural regions. As expected, we find a positive relationship between the national CRP enrollment cap and CRP acreage, as a 1% increase in the national cap increases CRP acreage by 0.09%.…”
Section: Resultsmentioning
confidence: 87%
“…Due to computational challenges resulting from missing data and zero enrollment in some counties during the analysis, counties in the Atlantic and Western regions were excluded. Furthermore, the exclusion of these regions is supported by a recent study by Cornish et al (2022), which reveals an insignificant connection between CRP rental payments and CRP land acreage in the Atlantic and Western parts of the United States. 5 The ideal situation is to separate the acreage data into their respective signups and subprograms due to the differing objectives of the program.…”
Section: Endnotesmentioning
confidence: 91%
See 3 more Smart Citations